Maximizing Online Marketing Strategy with Digital Advertising - Wuisan, Dewi Surya; Handra, Tessa (Startupreneur Business Digital (SABDA Journal), 2023)
The growth of the internet is altering business practices, notably those in retail establishments where company models use electronic commerce to handle transactions. This study's goal is to investigate the best practices for online advertising implementation and capturing consumer interest in purchasing. Additionally, this study used a descriptive survey method with verification. With a sample size of 96 customers, the population in this study consists of Lazada users in the city of Bandung. The results demonstrate that the use of online advertising has a direct influence on customers' intent to purchase through the Lazada website. The rapid development of information technology has had an impact on community in supporting various business activities, both large and small, so that they can be widely recognized global. The most obvious impact is that apart from being known, it can also increase sales volume and profit. Digital Marketing is one of the marketing media that has a huge impact. With using digital marketing in this case is social media, especially in every e-commerce application to increase sales, especially in the era of globalization social media affects so sales volume has increased rapidly compared to the old way of selling. Digital marketing is seen as the best media as the most effective means of promotion and efficiently and able to increase sales volume significantly.